Development of an LDR-integrated PDLC film for automatic glare reduction in vehicles - Riyan Ikhsan Nugroho; Marcin Noga; Naufal Annas Fauzi (Universitas Negeri Yogyakarta, 2025)
The high risk of glare from vehicle headlights at night often becomes a significant contributor to traffic accidents, particularly for motorcyclists and drivers of lightweight vehicles. To address this issue, a smart glare-blocking system based on a PDLC (Polymer Dispersed Liquid Crystal) film has been developed. This research proposes the design, development, and testing of a PDLC film system integrated with an LDR (Light-Dependent Resistor) sensor to automatically detect light intensity and adjust the film's opacity in real-time. The goal is to enhance driver visibility and comfort without compromising overall road safety. The experimental setup involved placing the prototype system at varying distances (0–9 meters) from a controlled light source at night. Measurements were conducted to collect data on light intensity, voltage output, resistance of the LDR, and the degree of light attenuation achieved by the PDLC film. The results showed that at a distance of 1 meter, the PDLC film could block up to 99.85% of incoming light, reducing 12080 Lux to only 17 Lux. Moreover, the film began to react at 6 meters with an output voltage of 34V. It became fully transparent at 8–9 meters with an output of 50V. The findings demonstrate that the PDLC system functions effectively in detecting potential glare and reducing its impact before it reaches the driver's eyes. This intelligent system offers a promising solution for minimizing night-driving hazards by dynamically adapting to changing light conditions.